2015
DOI: 10.3892/mco.2015.687
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of head and neck squamous cell carcinoma patient tolerance to high-dose cisplatin in concurrent chemoradiotherapy

Abstract: Abstract. Although high-dose cisplatin is the standard regimen of concurrent chemoradiotherapy (CCRT) for locally advanced head and neck squamous cell carcinoma (HNSCC), varying levels of patient tolerance towards cisplatin have been reported, and the predictive factors of cisplatin tolerance remain to be elucidated. The present study retrospectively reviewed newly diagnosed HNSCC patients who received CCRT. Cisplatin ; OR, 2.21; P=0.032) were significantly predictive of high-dose cisplatin tolerance. The high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In cancer specialty hospitals in Japan, 50% of patients receiving this same regimen have been reported to tolerate 3 courses of CDDP, and CR rate was 74%. 6 The present results compared with those data suggest that CRT using generic CDDP can be well tolerated in clinical practice.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In cancer specialty hospitals in Japan, 50% of patients receiving this same regimen have been reported to tolerate 3 courses of CDDP, and CR rate was 74%. 6 The present results compared with those data suggest that CRT using generic CDDP can be well tolerated in clinical practice.…”
Section: Discussionsupporting
confidence: 59%
“… 5 However, from the standpoint of clinical tolerance, CDDP 80 mg/m 2 is often used even in cancer specialty hospitals in Japan. 6 Our hospital also uses 80 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 82 patients analyzed in this study, 21 (26%) patients developed renal impairment (Figure 1B). Previous studies have reported that a cumulative CDDP dose of approximately 200 mg/m 2 or more was sufficient to produce an antitumor effect in patients with head and neck cancer (7,26,27), and the therapeutic goals are set at a cumulative CDDP dose of 200 mg/m 2 or more. In this study, the renal impairment led to a much higher rate of dose reduction or discontinuation of CDDP administration in the second cycle (86% vs. 30%), a much lower completion rate of three cycles in CDDP-RT (24% vs. 75%), and a much lower rate of >200 mg/m 2 of total CDDP dosage (19% vs. 77%) compared to patients who did not develop renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, only 50% of patients tolerate the combination of cisplatin at high doses with radiotherapy [23]. This proportion of patients becomes even smaller when we consider that the majority of HNC patients have a low performance status and comorbidities, which are contraindications for cisplatin [24].…”
Section: Discussionmentioning
confidence: 99%